Cellular interplay in skeletal muscle regeneration and wasting: insights from animal models. Issue 2 (21st February 2023) - Henrot, Pauline; Blervaque, Léo; Dupin, Isabelle; Zysman, Maéva; Esteves, Pauline; Gouzi, Fares; Hayot, Maurice; Pomiès, Pascal; Berger, Patrick
Abstract: Skeletal muscle wasting, whether related to physiological ageing, muscle disuse or to an underlying chronic disease, is a key determinant to quality of life and mortality. However, cellular basis responsible for increased catabolism in myocytes often remains unclear. Although myocytes represent the vast majority of skeletal muscle cellular population, they are surrounded by numerous cells with various functions. Animal models, mostly rodents, can help to decipher the mechanisms behind this highly dynamic process, by allowing access to every muscle as well as time‐course studies. Satellite cells (SCs) play a crucial role in muscle regeneration, within a niche also composed of fibroblasts and vascular and immune cells. Their proliferation and differentiation is altered in several models of muscle wasting such as cancer, chronic kidney disease or chronic obstructive pulmonary disease (COPD). Fibro‐adipogenic progenitor cells are also responsible for functional muscle growth and repair and are associated in disease to muscle fibrosis such as in chronic kidney disease. Other cells have recently proven to have direct myogenic potential, such as pericytes. Outside their role in angiogenesis, endothelial cells and pericytes also participate to healthy muscle homoeostasis by promoting SC pool maintenance (so‐called myogenesis–angiogenesis coupling). Their role in chronic diseases muscle wasting has been less studied. Immune cells are pivotal for muscle repair after injury: Macrophages undergo a transition from the M1 to the M2 state along with the transition between the inflammatory and resolutive phase of muscle repair. T regulatory lymphocytes promote and regulate this transition and are also able to activate SC proliferation and differentiation. Neural cells such as terminal Schwann cells, motor neurons and kranocytes are notably implicated in age‐related sarcopenia. Last, newly identified cells in skeletal muscle, such as telocytes or interstitial tenocytes could play a role in tissular homoeostasis. We also put a special focus on cellular alterations occurring in COPD, a chronic and highly prevalent respiratory disease mainly linked to tobacco smoke exposure, where muscle wasting is strongly associated with increased mortality, and discuss the pros and cons of animal models versus human studies in this context. Finally, we discuss resident cells metabolism and present future promising leads for research, including the use of muscle organoids.